The teaching of the concept of tangent line using original sources - Mota, Catarina (2013)
FEDER Funds through "Programa Operacional Factores de Competitividade COMPETE" and by Portuguese Funds through FCT- "Fundação para a Ciência e a Tecnologia", within the project PEst-C/MAT/UI0013/2011